Hubungan Siklus Menstruasi dan Kecemasan dengan Performa Fisik pada Atlet Pencak Silat - Daviyati, Alya; Hidayat, Yusuf; Noviyanti Fajrah Ilsya, Marisa (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the relationship between the menstrual cycle and anxiety with physical performance in pencak silat athletes. This study used a correlational design with a sample of 30 pencak silat athletes. Data were collected using the Menstrual Disturbance Questionnaire (MEDI-Q) to measure menstrual disorders, the Competitive State Anxiety Inventory-2 questionnaire to measure anxiety, and a physical condition test. Data analysis used the Pearson correlation test for bivariate relationships and multiple correlation tests to examine the relationship between the two independent variables and physical condition. The results of the Pearson correlation test showed that both menstrual disorders (p = 0.259) and anxiety (p = 0.802) had a significant effect. The multiple correlation test showed a Sig. F Change value of 0.529 (p > 0.05), indicating that the overall multiple correlation analysis was not statistically significant, with no significant relationship with physical performance. In conclusion, this study offers a new perspective in understanding the complexity of factors influencing the physical performance of pencak silat athletes. Keywords: Menstrual Cycle; Anxiety; Physical Performance; Athletes